Local Perspectives on the Use of Malagasy as a Language of Instruction in Madagascar’s Elementary Schools - Léa, Soameva; Angelo, Vahinimalala Tahinarizafy; Emynorane, Ralaivao Hanginiaina; Urbain, Marolahy Jacquot (Jurnal Pendidikan Tambusai, 2025)
This study aims to explore local perspectives on the use of Malagasy as a language of instruction in elementary schools in Toliara, Southwest Madagascar. Using a qualitative approach, data were collected through interviews, classroom observations, and informal discussions with teachers, school administrators, and parents to examine perceptions, challenges, and aspirations related to mother-tongue education. The findings reveal that the use of Malagasy enhances comprehension, participation, and cultural connection among learners, fostering a more inclusive and confident learning environment. Even so, the implementation process faces significant obstacles, including limited teaching materials, inadequate teacher training, and insufficient policy support. Participants expressed strong support for a balanced bilingual model that integrates Malagasy for foundational learning and French for broader academic and professional opportunities. The study emphasizes the need for clear policy direction, improved teacher preparation, and greater community involvement to strengthen the role of Malagasy in education. These insights contribute to broader discussions on linguistic equity and educational reform in multilingual societies, suggesting that sustainable progress requires aligning national identity with educational inclusiveness and global engagement.